2019
DOI: 10.2147/ijn.s231167
|View full text |Cite
|
Sign up to set email alerts
|

<p>Verteporfin-Loaded Anisotropic Poly(Beta-Amino Ester)-Based Micelles Demonstrate Brain Cancer-Selective Cytotoxicity and Enhanced Pharmacokinetics</p>

Abstract: Background: Nanomedicine can improve traditional therapies by enhancing the controlled release of drugs at targeted tissues in the body. However, there still exists disease-and therapyspecific barriers that limit the efficacy of such treatments. A major challenge in developing effective therapies for one of the most aggressive brain tumors, glioblastoma (GBM), is affecting brain cancer cells while avoiding damage to the surrounding healthy brain parenchyma. Here, we developed poly(ethylene glycol) (PEG)-poly(b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Modification of the surface of nanoparticles by conjugating neutral, water-soluble PEG molecules is a widely employed strategy to improve transport in physiological environments . We and other groups have reported that PEGylation not only reduces surface charge and thereby enhances potential safety of the vector , but also limits protein adsorption through steric hindrance, which allows for improved stability, , pharmacokinetics, and diffusivity into the brain parenchyma . These are important factors to enhance the distribution of the nanoparticles and enable a widespread effect against brain cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Modification of the surface of nanoparticles by conjugating neutral, water-soluble PEG molecules is a widely employed strategy to improve transport in physiological environments . We and other groups have reported that PEGylation not only reduces surface charge and thereby enhances potential safety of the vector , but also limits protein adsorption through steric hindrance, which allows for improved stability, , pharmacokinetics, and diffusivity into the brain parenchyma . These are important factors to enhance the distribution of the nanoparticles and enable a widespread effect against brain cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Verteporfin (VP) is a derivative of benzoporphyrin, a very hydrophobic molecule, and Yes-associated protein (YAP) inhibitor, expressed in tumors like GBM. VP was encapsulated in micelles of poly(ethylene glycol)-poly(β-amino ester)- poly(ethylene glycol) (PEG-PBAE-PEG) triblock copolymer [ 100 ] and tested against GBM cell lines. Two types of micelles were prepared to encapsulate the PV, spherical (sVPM) and filamentous (fVPM) micelles, using the nanoprecipitation method.…”
Section: Polymeric Nanosystemsmentioning
confidence: 99%
“…In addition, its mode of inhibition and mechanism of interaction with YAP remain unknown. Considering all, verteporfin might not be the most promising drug, nevertheless, some studies have shown that the loading of verteporfin into microparticles improves its specificity and pharmacokinetics, making it more suitable as a treatment (267)(268)(269). Similarly, the CA3 compound has been reported as a modulator of YAP/TEAD transcriptional activity through the inhibition of YAP, but it has drawbacks similar to those of verteporfin (270,271).…”
Section: Therapeutic Targets and Drugsmentioning
confidence: 99%